2018
DOI: 10.1002/jclp.22726
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous, depraved, and death‐worthy: A meta‐analysis of the correlates of perceived psychopathy in jury simulation studies

Abstract: Objectives: Experimental research suggests that legal defendants described as psychopathic are generally, although not uniformly, judged more negatively and punitively. Understanding the correlates of perceived psychopathy, regardless of exposure to mental health evidence, is an important step towards clarifying divergent findings. Method: We conducted a quantitative synthesis of ten juror simulation studies (combined N = 2,980) examining the meta-analytic association between perceived defendant psychopathy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…A separate meta-analysis by Kelley et al (2019) attempted to further understand the psychopathy labelling literature by looking at the effect of perceived psychopathy on various outcomes. Examining ten juror simulation studies, Kelley et al (2019) found that when participants perceived someone as being more psychopathic, they viewed that individual as being more dangerous (rw = 0.31), evil (rw = 0.44) and deserving of harsher consequences for capital sentencing (rw = 0.22) and sentence length (rw = 0.27).…”
Section: Psychopathy In the Criminal Justice Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…A separate meta-analysis by Kelley et al (2019) attempted to further understand the psychopathy labelling literature by looking at the effect of perceived psychopathy on various outcomes. Examining ten juror simulation studies, Kelley et al (2019) found that when participants perceived someone as being more psychopathic, they viewed that individual as being more dangerous (rw = 0.31), evil (rw = 0.44) and deserving of harsher consequences for capital sentencing (rw = 0.22) and sentence length (rw = 0.27).…”
Section: Psychopathy In the Criminal Justice Systemmentioning
confidence: 99%
“…These results demonstrated the importance of perceived psychopathy in experimental studies to help identify the circumstances under which psychopathy evidence might negatively impact legal outcomes. Further, the researchers suggested that it is possible that previous studies that failed to find a psychopathy labelling effect may not have sufficiently elicited differing perceptions of the defendant's level of psychopathy (Kelley et al, 2019).…”
Section: Psychopathy In the Criminal Justice Systemmentioning
confidence: 99%
See 3 more Smart Citations